Investigation of Annealing Temperature on Vanadium Dioxide Thin Films - Hashim, Hashimah; Rafiq Roslan, Muhammad; Mohd Yazid, Ibrahim (International Journal of Engineering and Technology, 2018)
Vanadium dioxide (VO2) thin film is a material that has multiple functionalities and smart response that give good news for device engineers and material scientist. One of the applications of VO2 thin film is for smart windows that could help to reduce the impact of global warming from buildings and to reduce expenditure on equipment or other methods to cool buildings. Annealing temperature is one of the importance parameters in VO2 thin films fabrication. The optimum annealing temperature is required in order to produce good properties of thin films. In this research, the properties of VO2 thin films were examined. All samples were prepared by the sol-gel spin coating method. The thin films were annealed at different annealing temperatures of 475ËšC, 500ËšC, 525ËšC, 550ËšC and 575ËšC.Â The properties of thin film in term of structural, optical and electrical properties were investigated by using field emission scanning electron microscope (FESEM), ultraviolet-visible (UV-Vis-NIR) spectrometer and Current-Voltage measurement respectively. FESEM was used to produce the images of the samplesâ€™ structure, the diameter of each nanoparticle and the thickness of samples. An I-V two-probe instrument was used to characterize the electrical properties of VO2 thin films with calculated resistivity and conductivity due to the differentiation of annealing temperature. An ultraviolet-visible spectrometer was used to characterize the optical properties of VO2 thin film; to show the absorbance and transmittance plots as well as calculated energy band gap. The results show that the thickness and the grain size of the thin films increase with annealing temperature. However, the increase in the absorbance and transmittance is inversely proportional to the annealing temperature.Â Â